2014
DOI: 10.3917/seve.043.0039
|View full text |Cite
|
Sign up to set email alerts
|

Inégalités géographiques de santé en France

Abstract: Cet article se propose d’affirmer la pertinence d’une approche des déterminants de la santé par les inégalités de santé. Les comparaisons sanitaires entre populations et entre lieux, ainsi que leurs évolutions, débouchent en effet sur l’identification des facteurs explicatifs de situations et de dynamiques contrastées.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…A previous study in Paris, by Vallée et al in 2010 demonstrated that unequal participation in preventive healthcare in urban areas may not be directly associated with the spatial distribution of the services, with a notable exception for people with limited activity space for example, for a highly deprived population who cannot afford to travel by car [ 43 ]. Similarly, in France, Rican et al [ 44 ] indicated that low residential mobility due to inappropriate urban planning for pedestrians could curb participation rates.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in Paris, by Vallée et al in 2010 demonstrated that unequal participation in preventive healthcare in urban areas may not be directly associated with the spatial distribution of the services, with a notable exception for people with limited activity space for example, for a highly deprived population who cannot afford to travel by car [ 43 ]. Similarly, in France, Rican et al [ 44 ] indicated that low residential mobility due to inappropriate urban planning for pedestrians could curb participation rates.…”
Section: Discussionmentioning
confidence: 99%
“…Mais ces disparités territoriales n'ont pas toujours été du même ordre : le Nord de la France a ainsi connu des espérances de vie plus élevées, jusqu'à la dégradation de sa situation sanitaire dans les années 1970. À l'inverse, avec le développement de ses pôles urbains, la Bretagne a vu son espérance de vie augmenter depuis le milieu du 20ème siècle (Rican et al, 2014). Les inégalités spatiales de mortalité se montrent ainsi très liées à la situation socioéconomique des territoires, et sont en constante évolution.…”
Section: Introductionunclassified